Hermeneutical Analysis of Simplification and Distortion in @Officialfiqihpernikahan on TikTok: A Study of Hadiths on Prophetic Marriage - Dyna Tauhidah; Ida Rochmawati; Mahfidzatun Nabilah; Khoiriyah Dwi Safitri (JURNAL AT-TURAS, 2025)
This study stems from concerns over the practice of presenting marriage hadith on TikTok, especially the "Marriage ala Rasulullah" series by @Officialfiqihpernikah, which ignores the Arabic text and often misstates the source of transmission, thus creating the potential for distortion of meaning in the context of digital da'wah which demands a short and interesting format. The purpose of the study is to analyze the authenticity of the sanads of six hadith contents and reveal the changes in meaning that occur due to the logic of social media. This study used a qualitative approach with two main methods: (1) sanad criticism to assess the validity of the hadith; and (2) content analysis based on Stig Hjarvard's theory of religious mediatization to understand the transformation of meaning in the logic of social media. The primary data consisted of six video clips on the account, while hadith literature, digital da'wah, and mediatization theory served as secondary data; the analysis was conducted through data reduction, classification based on mediatization elements (such as media logic, banal religion, and protagonist narrative framework), and verification of the chain of transmission. The findings reveal that the hadith reported by @Officialfiqihpernika contain data reduction, textual simplification, narration errors and meaning errors. This research contributes to the discourse of contemporary hadith criticism in the digital landscape and offers a model for evaluating sanad-based da'wah content and media logic. These results can be used to design collaborative guidelines between content creators and academics in curating Islamic content on social media.